A new concept of a hybrid trapped field magnet lens. (7th March 2018) - Takahashi, Keita; Fujishiro, Hiroyuki; Ainslie, Mark D
Abstract: In this paper, a new concept of a hybrid trapped field magnet lens (HTFML) is proposed. The HTMFL exploits the 'vortex pinning effect' of an outer superconducting bulk cylinder, which is magnetized as a trapped field magnet (TFM) using field-cooled magnetization (FCM), and the 'diamagnetic shielding effect' of an inner bulk magnetic lens to generate a concentrated magnetic field higher than the trapped field from the TFM in the bore of the magnetic lens. This requires that, during the zero-field-cooled magnetization process, the outer cylinder is in the normal state ( T > superconducting transition temperature, T c ) and the inner lens is in the superconducting state ( T  <  T c ) when the external magnetizing field is applied, followed by cooling to an appropriate operating temperature, then removing the external field. This is explored for two potential cases: (1) exploiting the difference in T c of two different bulk materials ('case-1'), e.g. MgB2 ( T c  = 39 K) and GdBaCuO ( T c  = 92 K) or (2) using the same material for the whole HTFML, e.g., GdBaCuO, but utilizing individually controlled cryostats, the same cryostat with different cooling loops or coolants, or heaters that keep the outer bulk cylinder at a temperature above T c to achieve the same desired effect. The HTFML is verified using numerical simulations for 'case-1' using an MgB2 cylinder and GdBaCuO lens pair and for 'case-2' using a GdBaCuO cylinder and GdBaCuO lens pair. As a result, the HTFML could reliably generate a concentrated magnetic field B c  = 4.73 T with the external magnetizing field B app  = 3 T in the 'case-1', and a higher B c  = 13.49 T with higher B app  = 10 T in the 'case-2', respectively. This could, for example, be used to enhance the magnetic field in the bore of a bulk superconducting NMR/MRI system to improve its resolution.